2023
DOI: 10.1001/jamainternmed.2023.4832
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Emergency Department Physical Restraint Use

Vidya Eswaran,
Melanie F. Molina,
Alison R. Hwong
et al.

Abstract: ImportanceRecent studies have demonstrated that people of color are more likely to be restrained in emergency department (ED) settings compared with other patients, but many of these studies are based at a single site or health care system, limiting their generalizability.ObjectiveTo synthesize existing literature on risk of physical restraint use in adult EDs, specifically in reference to patients of different racial and ethnic backgrounds.Data SourcesA systematic search of PubMed, Embase, Web of Science, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…We only included those covariates that had a theoretical or practical connection. For instance, studies have identified race as a risk factor for patients being physically restrained, 19 and older hospitalized patients who required PRs have been found to have longer hospital stays. 20 Some studies also suggest males, perhaps because of greater overall strength, are more frequently physically restrained.…”
Section: Methodsmentioning
confidence: 99%
“…We only included those covariates that had a theoretical or practical connection. For instance, studies have identified race as a risk factor for patients being physically restrained, 19 and older hospitalized patients who required PRs have been found to have longer hospital stays. 20 Some studies also suggest males, perhaps because of greater overall strength, are more frequently physically restrained.…”
Section: Methodsmentioning
confidence: 99%
“…Though the field has come so far, and there has been action induced from across multiple disciplines, and the Global Alliance has been part of that history to make a much-needed change, there is still so much more change that is needed. There are still great disparities for those with SMI and experiences of marginalization, stigma, oppression, trauma and death, and racism, impacting outcomes for those with SMI (Daniels et al, 2023; Eswaran et al, 2023; Frueh et al, 2005; Kersting et al, 2019; Perlin, 2013; Smith et al, 2022; Sturmey, 2015; Waldemar et al, 2019). For example, those with SMI are more likely to be put in restraints just because they have a diagnosis of schizophrenia (in comparison to those without that diagnosis) despite no prior history of violence or indication of current violence upon presentation to an emergency room in crisis, with higher incidents among individuals who are Black (Daniels et al, 2023; Eswaran et al, 2023).…”
Section: Future Action For Addressing Social Justice Action In Mental...mentioning
confidence: 99%
“…There are still great disparities for those with SMI and experiences of marginalization, stigma, oppression, trauma and death, and racism, impacting outcomes for those with SMI (Daniels et al, 2023; Eswaran et al, 2023; Frueh et al, 2005; Kersting et al, 2019; Perlin, 2013; Smith et al, 2022; Sturmey, 2015; Waldemar et al, 2019). For example, those with SMI are more likely to be put in restraints just because they have a diagnosis of schizophrenia (in comparison to those without that diagnosis) despite no prior history of violence or indication of current violence upon presentation to an emergency room in crisis, with higher incidents among individuals who are Black (Daniels et al, 2023; Eswaran et al, 2023). Sadly, a recent review of coercive measures in hospitals continues to report documented deaths due to restraints in over 42 studies reviewed (Kersting et al, 2019).…”
Section: Future Action For Addressing Social Justice Action In Mental...mentioning
confidence: 99%
See 2 more Smart Citations